THE CONTRIBUTION OF ACADEMIC PROCRASTINATION TO STUDENT LEARNING ACHIEVEMENT AND THE IMPLICATIONS IN PROGRAM COUNSELING AND COUNSELING SERVICES - Miswanto Miswanto (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract: This research is motivated by the number of students who have low learning achievement. Academic procrastination is thought to be a factor that can affect student achievement. This study aims to describe the contribution of academic procrastination to student achievement. This study uses a quantitative approach with descriptive correlational and qualitative approaches. The research findings show that: (1) the picture of academic procrastination, student learning achievement is in the medium category (2) there is a significant negative contribution of academic procrastination to student achievement (3) the material related to reducing academic procrastination is partly contained in the BK program Class XI and XII SMA Pertiwi 1 Padang Academic Year 2016/2017 which have been compiled by the counseling teacher. Keywords: academic procrastination, learning achievementAbstrak: Penelitian ini dilatarbelakangi oleh banyaknya siswa yang memiliki prestasi belajar rendah. Prokrastinasi akademik dianggap sebagai faktor yang dapat mempengaruhi prestasi belajar siswa. Penelitian ini bertujuan untuk mendeskripsikan kontribusi prokrastinasi akademik terhadap prestasi belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan pendekatan deskriptif korelasional dan kualitatif. Hasil penelitian menunjukkan bahwa: (1) gambaran prokrastinasi akademik, prestasi belajar siswa termasuk dalam kategori sedang (2) terdapat kontribusi negatif yang signifikan antara prokrastinasi akademik terhadap prestasi belajar siswa (3) materi terkait pengurangan prokrastinasi akademik sebagian tertuang dalam program BK Kelas XI dan XII SMA Pertiwi 1 Padang Tahun Ajaran 2016/2017 yang telah disusun oleh guru BK.Kata kunci: prokrastinasi akademik, prestasi belajar